Intra-amniotic Infection Caused by Capnocytophaga Species - Hiroshige Mikamo; Kyoko Kawazoe; Yasumasa Sato; Koji Izumi; Teruhiko Tamaya (Hindawi Limited, 1996)
Background: Capnocytophaga species are common oral pathogens and infrequent causes of systemic infection in patients with compromised host. The isolation of this organism suggests an oral source of infection.